Solid Waste and Landfills Management Recent Advances - Zailani, Suhaiza; Sarvajayakesavalu, Suriyanarayanan (IntechOpen, 2023)
Solid Waste and Landfills Management - Recent Advances outlines the fundamental ideas and most recent developments for managing solid waste in an environmentally responsible manner. Globally, the quantity of solid trash is increasing, but its environmental impact is also a concern, especially with the advent of elements that are detrimental to ecosystems. This book examines all aspects of solid waste from a global perspective, including waste minimization, waste as a resource, proper disposal, and efficient systems promoted by sound public policy. It includes eight chapters written by eminent specialists that examine the essential topics to be considered during the various phases of a waste management program. Among the topics covered in this book are public policies focusing on reducing waste at its source, recycling, and minimizing disposal amounts; technologies for treating and recycling solid waste; safe, efficient treatment and disposal of hazardous and other special wastes; development and maintenance of engineered landfills and landfill mining; and legal frameworks and the use of life-cycle assessment as a tool for the waste management industry. This book is an indispensable resource for municipal engineers, environmental managers, researchers, students, policymakers, and planners interested in social and technological challenges connected to sustainable solid waste management.